The Proletariat Class Struggle Portrayal In AKMU’S Dinosaur: Marxism Approach - Meutia Sani, Sitti Kamila; Lirishati Soethama, Putu; Detriasmita Saientisna, Made; Seri Malini, Ni Luh Nyoman (Loquēla (Journal of Linguistics, Literature, and Education), 2023)
This research discusses the portrayal of the proletariat social class in AKMU's song entitled Dinosaur. This descriptive qualitative research focuses on finding out the class struggle suffered by the proletariat class in South Korea due to the 1998 monetary crisis portrayed by the lyrics of Dinosaur by AKMU, from the Marxism theory by Karl Marx. The song title Dinosaur itself is a metaphor in the context of debt collectors. On that account, the view of the proletariat social class put forward by Karl Marx (1867) is a propitious match for a song analysis in Dinosaur by AKMU. Data were collected by observing the lyrics, music videos, and related interviews with AKMU as the writer, composer, and singer. The data was flocked together by the note-taking approach to discover data to latch onto valid information related. The conclusion shows that Dinosaur by AKMU portrays economic conditions between the proletariat and the ubiquitousness of debt collectors in South Korea due to the 1998 monetary crisis. The solidity of the debt collector industry was bolstered by the emergence of families from the lower middle class who have entangled in the instability of the poverty rate in South Korea at the time the song Dinosaur was released.